Bibliometric Mapping of Islamic Green Economy Research: Trends, Networks, and Emerging Themes - Ainul Fatha Isman; Syahriyah Semaun; Muh. Ahsan Kamil; Ali Wardani; Muhammad Rasyid Ridlo (Yayasan Darussalam Patalassang, 2025)
The rapid growth of the global Islamic economy, with Sharia financial assets projected to reach USD 9.75 trillion by 2029, demands the transformation of Sharia accounting systems through artificial intelligence (AI) implementation. This study analyzes the impact of AI on the transformation of Sharia accounting systems from a global perspective using qualitative methods through library research examining recent academic sources. The results reveal that AI enhances Sharia compliance monitoring accuracy by up to 92% through natural language processing (NLP), but faces complex challenges including regulatory disparities, algorithmic biases, and technological infrastructure gaps between GCC, Southeast Asia, and Africa regions. Key findings emphasize the need for an ethical framework based on maqasid al-shariah and localized AI adoption strategies. The research contributes to the development of a hybrid intelligence model integrating AI with human expertise and an ethical AI certification framework for Sharia accounting. This study recommends multisectoral collaboration to ensure digital transformation aligned with Islamic values.